A New Minoan-Type Peak Sanctuary on Stelida, Naxos - Carter, Tristan; Mallinson, Kristine; Mastrogiannopoulou, Vagia; Contreras, Daniel A.; Diffey, Charlotte; Lopez, Claudette; Pareja, Marie N.; Tsartsidou, Georgia; Athanasoulis, Dimitris (Journal of Greek Archaeology, 2021)
A long-recognised characteristic of Crete’s later Bronze Age [BA] state-level society – the ‘Minoan civilization’ of the 2nd millennium cal. BC – was the establishment of socio-economic connections with off-island populations. The nature of these relationships has been interpreted in various ways, from the establishment of overseas colonies to a more mutually beneficial relationship between local political agents and their Cretan partners, not least Knossos. Minoan influence has been documented throughout the southern Aegean in the form of material culture, iconography, metrological systems and socio-religious practices. It is the latter theme that concerns us here, specifically in the form of ‘peak sanctuaries’, i.e. upland foci of ritual activity associated with settlements and palatial centres throughout Crete, a handful of which are claimed to have been established overseas, on Kythera, Kea, Naxos, Rhodes and possibly Andros (Figure 1). We report here on what we claim to be a new example from Stelida on Naxos, whose southern peak dominates the skyline of nearby Grotta, the island’s main harbour and BA centre (Figures 1-3). The argument is based upon (i) the character of the finds, (ii) the presence of architecture and (iii), the site’s location and the vistas afforded from it, all of which have excellent comparanda from recognised peak sanctuaries in Crete (Table 1). We start by providing a brief overview of peak sanctuaries, followed by a presentation of the new excavations at Stelida, after which we discuss the site’s larger significance, arguing that these new discoveries suggest that Naxos was a much more dynamic participant in relations with communities in Neopalatial Crete – not least Knossos than hitherto suggested.